ANALISIS PENCATATAN DAN PELAPORAN KAS PADA DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN ROKAN HULU - Susanti; Nurhayati (Program Studi Akuntansi Universitas Pasir Pengaraian, 2022)
The purpose of this study was to analyze cash records at the Department of Education, Youth and Sports of Rokan Hulu Regency and to analyze cash reporting at the Department of Education, Youth and Sports of Rokan Hulu Regency. The data analysis technique use in this research is descriptive method, namely the data obtained and then arranged in such a way that it can be analyzed correctly and thoroughly based on theories relevant to the problem for further conclusions drawn. Based on the results of the study, it was shown that the cash recording carried out by the Expenditure Treasurer of the Department of Education, Youth and Sports of Rokan Hulu Regency in general had followed the provisions contained in the Regulation of the Directorate General of Treasury Number Per 47/PB/2009. Likewise, cash reporting (Accountability Report) by the Expenditure Treasurer at the Department of Education, Youth and Sports of Rokan Hulu Regency in general has followed the provisions contained in the Regulation of the Directorate General of Treasury Number Per47/PB/2009. Thus it can be said that the recording and reporting of cash is in accordance with the provisions contained in the Regulation of the Directorate General of Treasury Number Per-47/PB/2009, meaning that the hypothesis made can beaccepted.